Heavy metal levels of drinking water in bitlis province - Tahir Kahraman; Süleyman Alemdar; Mustafa Alişarlı; Sema Ağaoğlu (Eurasian Journal of Veterinary Sciences)
Aim: This study was conducted to detect some heavy metal levels of drinking water in Bitlis city. Materials and Methods: A total of 164 water samples, collected from the tank and tap water of Bitlis and its provinces in autumn and spring were used as material. Element analysis (Fe, Mn, Cu, Zn, Cd, Ni, Pb and Co) was performed by flame atomic absorption spectrophotometer. Results: According to the results, the mean levels of Fe (6.67 μg/L), Mn (3.88 μg/L), Cu (7.52 μg/L), Zn (28.2 μg/L) and Cd (2.58 μg/L) were found to be in conformity with the drinking water standards. However, the mean levels of Pb (spring: 68.4 μg/L; autumn: 47.0 μg/L) and Co (spring: 44.2 μg/L; autumn: 11.9 μg/L) in both seasons, and Ni levels only in spring (40.1 μg/L) were higher than the related regulations. The effects of season on Fe, Zn, Cd, Ni, Pb and Co levels were found statistically significant (p<0.05). Conclusion: Considering the overall situation of the region and research findings, it is very important to the protection of existing water sources and routinely run water quality analysis, especially in drinking water in terms of public health.